After great pain a formal feeling comes. Quelques notes sur la formalisation lyrique du trauma - Antoine Cazé (Sillages Critiques)
In this article, I first analyze the primordial link between lyric poetry and trauma, existing from the Greek origins of the genre. Far from merely giving voice to a unified subject, the lyric poem relies on a foundational disjunction in its mode of address, which I propose to see as a figural trace of a wound. Consequently, it appears to be a wounded form rather than a way of expressing the vulnerability of the speaking subject. I then move on to a close reading of one poem by Emily Dickinson—“After great pain a formal feeling comes”—to throw into relief the writing strategies allowing the poetic form to contain traumatic pain, both physical and psychological, caused by death.